ASSOCIATION OF TLR 5 AND ESCHERICHIA COLI FLIC POLYMORPHISMS WITH RECURRENT URINARY TRACT INFECTIONS IN WOMEN - Z. J. Kadhim; G. A. Abdulhasan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to investigate the role of some Toll-like receptor 5 (TLR5) and E. coli fliC gene polymorphisms with increased risk to recurrent urinary tract infections (rUTI). From 180 specimens (blood and urine) were collected from women of different age, 60 of them serve as control while 120 had rUTI symptoms. After culturing of urine specimens, 43 (35.8%) were identified as E. coli isolates. Four SNPs were identified when amplified and sequenced of TLR5 include rs5744168, rs775385356, rs2072493 and rs5744174. Twelve flagellar antigen serotypes were obtained from fliC sequence of 28 isolates. By using Expasy and Clustal Omega programs, the FliC proteins of H-serotypes arranged in different lengths ranging between 324-634 residues. The N-terminal and C-terminal were conserved region, in contrast, the central region was variable poorly preserved. The results also showed list of conserved amino acids in both FliC termini included L89, Q90,R91, L95, Q98, N101 and E115 in N- terminus in all studied serotypes. Further, the N277 residue that reported its central role for TLR5 interaction were found in some serotypes. Indeed, it was no distinct relation between genotypes or allele frequencies with fliC polymorphisms found in E. coli isolated from rUTI.